Rhetorical And Grammatical Cohesion In The Lion King Movie Script - O, Oktaviany (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
The objectives of this research were to identify the types of grammatical and lexical cohesive devices used in The Lion King Movie Script, to describe the grammatical and lexical cohesion devices used in The Lion King Movie Script and to investigate the grammatical and lexical cohesion devices used in The Lion King Movie Script. The researcher used descriptive qualitative method to obtain the objectives of the research. The data of this research was grammatical and lexical cohesion while the data source of this research was script of The Lion King Movie. The results in this research were found 312 ties of grammatical cohesive devices and 196 lexical cohesive devices used in the script. The realization of cohesive devices used in The Lion King Movie script was semantic concept between lexical and grammatical cohesion devices, this referred to the relationship meaning that exists within or outside the text. The most types of grammatical cohesion used werepersonal reference and demonstrative reference because they used to refer something which was mentioned elsewhere in the script. Meanwhile, clausal substitution as only type of grammatical cohesion didnt occur in the whole scene. The most types of lexical used were repetition because they used to rewrite an item in preceding element with the same form to following element. Finally, the findings showed almost all types of lexical and grammatical cohesion contained reference, substitution, ellipsis, conjunction, repetition, synonymy, antonymy, hyponymy, meronymy, and collocation contained in The Lion King Movie script.